Femtosecond PLD-grown YF3 nanoparticle thin films as improved filterless VUV photoconductive detectors. (8th October 2020) - Yu, Xi; Cadatal-Raduban, Marilou; Kato, Seiya; Kase, Masahiko; Ono, Shingo
Abstract: A photoconductive detector (PCD) responding only to vacuum ultraviolet (VUV) radiations below 180 nm without any filter was fabricated using an yttrium fluoride (YF3 ) thin film grown by femtosecond (fs) laser pulsed laser deposition (PLD). The structural morphology (particle size and surface roughness) of the thin film was improved using a low laser fluence and a high substrate temperature during the fabrication. The smallest average particle size achieved was 159 nm with a roughness of 37 nm at a laser fluence of 13.5 J cm −2 and a substrate temperature of 400 °C. The resistances for the dark current of the PCD increased from 10 TΩ to 680 TΩ using YF3 thin films with a smaller average nanoparticle diameter of 159 nm rather than 330 nm. The time response of the PCD to a VUV flash lamp emitting at 170 nm showed that a small average nanoparticle diameter results to a fast response time. By covering the Al electrode pairs with another fs PLD-grown YF3 film, the influence of external photoelectric effect was suppressed and the response wavelength edge decreased from 280 nm to 180 nm without any filter. The filterless PCD is expected to enhance the use of fluoride thin films in conjunction with VUV light sources for various scientific and industrial applications.